Fishing Range Based on Spreads of Chlorophyill-a in Rupat Strait using Aqua-Modis Satellite Image - Sitorus, Gideon Dody Tama; Rifardi, Rifardi; Mubarak, Mubarak (Journal of Coastal and Ocean Sciences, 2022)
The study aims to know the area of fishing in the waters of the Strait based on a flat-out chlorophyill-a satellite image of AQUA-Modis. Data analysis uses Seadas 7.5.1 and Surfer 13. In this study the method used was the survey method. Ground checks are done aimed at directly knowing the water quality parameters. And also there is a documented documentary on the waters. Parameters measured in this study are those of the quality of the water covering: brightness, temperature, the velocity of the current, acidity (pH) and salinity. The measured parameters for the quality of water in the Dumai Waters were carried out at 3 stations that are thought to represent the parameters of the waters in Dumai. The result of the measured parameters for the quality of the Dumai Waters is known that for the value of the brightness of the Dumai waters is between 7.5 to 16 cm, the water temperature is between 28-29oC, the degree of acidity (pH) of water ranges between 6-7 and the salinity of the water is 26-32 0/00.The chlorophyill-a concentration in the Dumai waters based on analysis of the AQUA-Modis satellite image ranging from 4.001 to 11200 mg/m3. The level of fishing area in the Dumai Waters is 75%.